The impact of diabetic retinopathy: understanding the patient's perspective. Issue 6 (12th October 2010) - Fenwick, E K; Pesudovs, K; Rees, G; Dirani, M; Kawasaki, R; Wong, T Y; Lamoureux, E L
Abstract : Understanding the impact of a condition from the patient's perspective is important, and different types of patient-reported outcomes or instruments are available to help with this. This review article summarises the current evidence on the impact of diabetic retinopathy (DR) and its associated vision impairment on patient-reported outcomes. We have included research that has used a range of outcome measures to assess the impact of DR on generic health-related quality of life, utility, vision-functioning and vision-specific quality of life. This review also offers clarification on frequently misused psychometric terminologies to help clinicians and researchers better understand the literature associated with patient-reported outcome research. Overall, the evidence suggests that DR, particularly in its vision-threatening stages, has a substantial, negative impact on the patient. However, our understanding of the impact of DR is currently restricted due to limitations inherent in currently available patient-reported outcome measures. We conclude by discussing potential directions for future research in this area, such as item banking and computer adaptive testing.